Maternal Age at First Childbirth and Geographical Variation in Hepatitis B Virus Prevalence in Cameroon: Important Role of Mother-to-Child Transmission. (14th June 2021) - Moutchia, Jude; Njouom, Richard; Rumpler, Eva; Besombes, Camille; Texier, Gaëtan; Tejiokem, Mathurin; Crépey, Pascal; Fontanet, Arnaud; Shimakawa, Yusuke
Abstract: Background: The prevalence of hepatitis B virus (HBV) infection varies geographically around the world. Yet, its underlying mechanisms are unknown. Using a nationally representative population-based sample from all 58 administrative divisions in Cameroon, we examined the association between median maternal age at first childbirth in a preceding generation, a proxy for the frequency of mother-to-child transmission (MTCT) of HBV in a region, and the risk of chronic HBV infection, defined as positive surface antigen (HBsAg), in the index generation. Methods: We estimated a division-specific median maternal age at first childbirth using Demographic Health Surveys (DHSs) conducted in 1991, 1998, 2004, and 2011. We tested HBsAg in 2011 DHS participants. We used maps to display spatial variation. Results: In 14 150 participants (median age, 27 years; 51% females), the overall weighted prevalence of HBsAg was 11.9% (95% confidence interval [CI], 11.0 to 12.8), with a wide geographical variation across the divisions (range, 6.3%–23.7%). After adjusting for confounders and spatial dependency, lower maternal age at first childbirth was significantly associated with positive HBsAg at the division level (β, 1.89; 95% CI, 1.26 to 2.52) and at the individual level (odds ratio, 1.20; 95% CI, 1.04 to 1.39). A similar ecological correlation was observed across other African countries. Conclusions: The significant association between the maternal age at first childbirth and HBsAg positivity suggests a crucial role of MTCT in maintaining high HBV endemicity in some areas in Cameroon. This underlines an urgent need to effectively prevent MTCT in sub-Saharan Africa. Abstract : A marked spatial variation in hepatitis B virus (HBV) prevalence was observed in Cameroon. Maternal age at first childbirth was significantly associated with HBV positivity, suggesting a crucial role of HBV mother-to-child transmission in maintaining high HBV endemicity